NtGNL1a ARF-GEF acts in endocytosis in tobacco cells - Jelínková, Adriana; Müller, Karel; Fílová-Pařezová, Markéta; Petrášek, Jan (Bmc plant biology, 2015)
BACKGROUND: Processes of anterograde and retrograde membrane trafficking play an important role in cellular homeostasis and dynamic rearrangements of the plasma membrane (PM) in all eukaryotes. These processes depend on the activity of adenosine ribosylation factors (ARFs), a family of GTP-binding proteins and their guanine exchange factors (GEFs). However, knowledge on the function and specificity of individual ARF-GEFs for individual steps of membrane trafficking pathways is still limited in plants. RESULTS: In this work, treatments with various trafficking inhibitors showed that the endocytosis of FM 4-64 is largely dynamin-dependent and relies on proteins containing endocytic tyrosine-based internalization motif and intact cytoskeleton. Interestingly, brefeldin A (BFA), reported previously as an inhibitor of anterograde membrane trafficking in plants, appeared to be the most potent inhibitor of endocytosis in tobacco. In concert with this finding, we demonstrate that the point mutation in the Sec7 domain of the GNOM-LIKE protein1a (NtGNL1a) confers intracellular trafficking pathway-specific BFA resistance. The internalization of FM 4-64 and trafficking of PIN-FORMED1 (PIN1) auxin efflux carrier in BY-2 tobacco cells were studied to reveal the function of the ARF-GEF NtGNL1a in these. CONCLUSIONS: Altogether, our observations uncovered the role of NtGNL1a in endocytosis, including endocytosis of PM proteins (as PIN1 auxin efflux carrier). Moreover these data emphasize the need of careful evaluation of mode of action of non-native inhibitors in various species. In addition, they demonstrate the potential of tobacco BY-2 cells for selective mapping of ARF-GEF-regulated endomembrane trafficking pathways.
Keywords: výměnné faktory guaninnukleotidů; Endocytosis; rostlinné proteiny; Pyridinium Compounds; Plant Proteins; endocytóza; transport proteinů; pyridinové sloučeniny; Nicotiana; Protein Transport; Plant Cells; Guanine Nucleotide Exchange Factors; rostlinné buňky; tabák; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds